Utilization Waste Materials to Synthesize Nano Al2O3-CaO Photocatalyst using Infused Red Guava Leaves (Psidium Guajava L.) - Rodiah, Siti; Aprilia, Riana; Ariesta, Nina (Al-Kimia, 2022)
Diazinon is a very toxic pesticide for animals and humans that is widely used in the agricultural sector, so this pollutant needs to be reduced or eliminated in the environment through photodegradation using photocatalysts derived from metal oxides. The catalytic activity of metal oxides is enhanced by adding a support material and increasing the surface area by reducing the particle size to nano size. In this study, kaolin as a source of Al2O3 and golden snail shells as a source of CaO which used to synthesize Al2O3-CaO nanoparticles (NPs) with a simple and environmentally friendly method using plant infusions. Synthesis of Al2O3-CaO NPs using infused red guava leaves (Psidium guajava L.) had been done by utilized the secondary metabolites as reducing agents and stabilizers in the nanoparticle synthesis. FTIR analysis confirmed the presence of alumina (Al-O) groups at wave numbers 850 – 650 cm-1 and CaO at 3642 cm-1. XRD analysis showed NPs Al2O3-CaO had cubic with the crystal size of 14.59 nm. The morphology of Al2O3-CaO NPs showed in the SEM pictures were agglomerated. Al2O3-CaO NPs degraded diazinon by 75% within 180 minutes under UV radiation. Thus, this research not only reduce waste material, but also reduces water pollutant.